Превращение смеси изобутана с изобутанолом в разветвленные высокооктановые углеводороды C8 на кислотных катализаторах - Брей, В.В.; Шаранда, М. Е.; Криль, А.А.; Стрелко, В.В. (Видавничий дім "Академперіодика" НАН України, 2008)
It is shown that the realization of the isobutanol dehydration reaction in the presence of isobutane over acid catalysts is accompanied by the formation of not only isooctenes but also isooctanes at 150–210 ◦С and 3–11 bar with their total yield up to 76 mol % from expended alcohol.